DEVELOPMENT OF INQUIRI-BASED LEARNING DEVICES FOR TRAINING STUDENTS’ SCIENCE PROCESS ON MATERIAL ELASTICITY - Sopacua, Venty; Prabowo, Prabowo; Sudibyo, Elok (JPPS (Jurnal Penelitian Pendidikan Sains), 2018)
This study aims to produce an inquiry-based physics learning device to train high school students science process skills on the subject of material elasticity. The research design uses Kemp model tested in three classes of class XI MIA- 1 , class XI MIA- 2 , and class XI MIA- 6 with total number of students of 90 in SMA Negeri 5 Ambon, second semester of  academic year 2017/201 8.  Group pretest-posttest design was used for test design.  Data analysis techniques used include, 1) Qualitative descriptive analysis including validation result, readability level, Lesson plan implementation, students’ activity, learning constraints, science process skill result , and response. 2) Parametric statistical analysis includes: normality test, homogeneity test, and t-test. Finding showed that, 1) validity of learning tools developed is categorized as valid ;  2) the effectiveness of instructional tools in terms of: (a) the attainment of science process skills in the three classes obtained a significant increase in science process skill on each indicator studied by the researcher; (b) The student's response to the device and the learning implementation is very positive with the highest percentage is with teacher guidance when working on worksheet. Based on the finding, physics learning device by using inquiry model to train the students' science process skill which has been developed has met the criteria of validity, practicality, and effectiveness that it is feasible to be used to train students' science process skills on materials elasticity